P155 Visualisation of Airway Nerves in Chronic Cough: Towards the Identification of the Human 'Cough Receptor'. (19th November 2012) - West, PW; Canning, BJ; Hilton, EC; Khalid, S; Holt, K; Abdulqawi, R; Woodcock, AA; Smith, JA
Abstract : Introduction: The spinal and vagal innervation of the respiratory tract is well defined, particularly in animals. These discoveries include the identification of pathways involved in provoking cough and descriptions of the guinea pig 'cough receptor'. However, many of the immunochemical features of the airway afferents described in animals have yet to be defined in humans, yet plasticity of these airway afferents may be important in the pathophysiology of chronic cough. Objectives: To define and characterise the innervation present in bronchoscopic biopsies from patients with chronic cough. We aimed to carry out the first ever whole mount immunohistochemical studies of airway nerves in cough patients, a technique that should improve visualisation of these neuronal structures and their sites of termination. Methods: Biopsy tissue was gifted from patients undergoing clinical investigation for chronic cough. Tissue, sampled from throughout the extrapulmonary airways, was immediately fixed in 4% paraformaldehyde. Non-specific antibody binding was blocked using 10% normal serum and 1% skimmed milk powder, diluted in PBS, before application of primary antibodies. Polyclonal rabbit anti-PGP9.5 (Ultraclone, UK) and monoclonal mouse anti-neurofilament (NF200, Leica Biosystems, UK) were applied at a dilution of 1:1000 and 1:200 respectively. Primary antibody binding was detected using appropriate Alexa-fluor conjugated secondary antibodies and whole mount preparations were visualised using epifluorescence and confocal microscopy. Images of biopsy staining were subject to morphometric analysis. Results: Many epithelial, subepithelial and intramuscular fibres were detected using both antibodies. Co-staining revealed that only PGP9.5 defined pulmonary neuroendocrine cells and better elucidated varicose epithelial fibres. A proportion of all fibre types were only immunopositive for one marker. Notably NF200 exclusively detected some epithelial fibres and a group of larger diameter neurons (Ø3–6 µm) some of which are consistent with observations of Aδ-fibre airway mechanoreceptors. Conclusions: We have described neuronal structures in whole-mount preparations of tissue from patients suffering from chronic cough. Notably, we described a population of PGP9.5 negative fibres within the airways. Some of these fibres are morphologically consistent with thinly myelinated Aδ-fibres described in animal models as 'cough receptors'. These ongoing studies could help define the plasticity of airway nerves in patients with chronic cough.